Pengembangan Bahan Ajar Digital Berbasis Quizizz Dalam Pembelajaran Puisi di SMK Jambi Medan - Tamba, Sania Naora br; Pinem, Kesya Ananda; Sintia, Gladys; Situmorang, Nadia Riska; Manik, Yohana; Azizah, Nurul; Hutagalung, Trisnawati (Journal of Education Religion Humanities and Multidiciplinary, 2025)
This study aims to develop Quizizz-based digital teaching materials for poetry learning at SMK Jambi Medan as a solution to students' low interest, motivation, and understanding of poetry material. The study uses the Research and Development (RD) method with the 4D model (Define, Design, Develop, Disseminate). During the definition stage, it was found that students had difficulty understanding the intrinsic elements of poetry and were not fully engaged in the learning process due to conventional teaching methods. During the design stage, a prototype of digital teaching materials was developed that combined poetry modules with interactive gamification-based exercises through the Quizizz platform. Expert validation confirmed that these teaching materials were suitable for testing with a few minor improvements. A limited trial involving 34 students showed very positive responses, with 88.2% of students rating learning using Quizizz as more interesting, interactive, and helpful in understanding poetry material effectively. The results of the study show that the integration of gamification technology can increase student engagement and understanding in poetry learning, so it is recommended to be implemented more widely in literature learning in vocational schools.